Pengembangan Pemasaran Produk Alat Kesenian Lokal di Dukuh Mirah Desa Nambangrejo Sukorejo Ponorogo - Dharoini, Amirul; Ansori, Teguh (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Most of the residents of Nambangrejo Village work as local cultural craft businesses. The problem in that place is that they are only able to market their products in the surrounding environment. This is what causes the business to take a very long time and is difficult to develop and become big. The purpose of this study is to create products that can be accepted by consumers in accordance with the targeted marketing strategy and develop the business on a larger scale. The method used is field research, namely the qualitative method. Its implementation is carried out by providing assistance in marketing and promoting local cultural craft businesses. The results obtained from the assistance, which were initially only in the environment, have now spread widely to other areas. So, as a conclusion in the training activity for developing marketing strategies for local cultural craft businesses, namely being able to understand insights about marketing strategies, having skills in marketing a local art tool product and how to make products that are currently acceptable in the market so that products can compete in terms of quality and marketing.